Letters from Jan cEp to Josef Tichy (an Edition with an Introduction to the Correspondence) - Komendova, Tereza (Bohemica Olomucensia, 2024)
This study provides the reader with the correspondence of Jan Cep to Josef Tichy, the editor of the Olomouc publishing house Velehrad and Cep's friend. The correspondence contains thirty-one letters and eight postcards sent by Jan Cep to Josef Tichy from 1939 to the end of 1947. The letters (together with Josef Tichy's memoirs of one of his visits to Myslechovice) are kept in the Memorial of Literature in Moravia in Rajhrad.
Keywords: Jan Cep; Josef Tichy; publishing house Velehrad; redactor; edition; correspondence